Cognitive rehabilitation in schizophrenia research: a bibliometric and visualization analysis - Shu, Xiaofeng; Dai, Yubin; Tang, Juanping; Huang, Yi; Hu, Rong; Lin, Yong (Frontiers in Psychiatry, 2024)
ObjectiveCognitive impairment is notably prevalent among schizophrenic individuals and is acknowledged as one of the core features of the disorder. Despite the proliferation of literature on cognitive rehabilitation treatments for schizophrenia in recent years, there remains a dearth of systematic reviews and selections of research in this area. From a bibliometric perspective, this study aims to analyze and discuss the current state, developmental trends, and potential research hotspots of cognitive rehabilitation in schizophrenia over the past two decades.MethodsThe Core database of Web of Science was utilized to retrieve articles on cognitive rehabilitation in Schizophrenia that were published from 2004 to 2024. Bibliometrics was applied to perform both quantitative and qualitative analyses of authors, institutions, countries, journals, references, and keywords, leveraging tools such as CiteSpace, VOSviewer, and the R software package Bibliometrix.ResultsA total of 2,413 articles were encompassed in this study, comprising 1,774 regular articles and 373 review articles. The United States emerged as the country with the highest productivity and citation counts, engaging in academic collaborations with over 40 nations. This was followed by the United Kingdom and Spain. King’s College London stood out as the leading institution in the field. However, the article with the highest average citation rate was authored by Susan R. McGurk from the Dartmouth Centre for Psychiatric Research in the United States. Schizophrenia Research proved to be the most influential journal in this domain, with its articles being cited over 10,000 times.ConclusionThis study provides a comprehensive review of research achievements in cognitive rehabilitation for schizophrenia spanning from 2004 to 2024, and outlines global research hotspots and trends with future projections. Currently, methods for cognitive rehabilitation in schizophrenia and neural plasticity in the brain represent the cutting-edge of research. The safety, efficacy, and standardization of virtual reality are poised to emerge as potential future hotspots and trends in research. Additionally, the neurobiological foundations of cognitive remediation therapy constitute an unexplored territory ripe for further investigation.